Mathematical Modeling and Analysis of a Hydrostatic Drive Train. Issue 1 (2015) - Zeman, P.; Kemmetmüller, W.; Kugi, A.
Abstract: Hydrostatic drives constitute an advantageous alternative to conventional mechanical gears with a fixed transmission ratio. The hydraulic part of the system decouples the input and output speeds of the drive and may serve as an energy storage for recuperation as well. For this reason, hydrostatic drives are a well-established concept, in particular in the field of mobile working machines such as lift trucks or excavators. In this work, a mathematical model for a hydrostatic drive train of a passenger vehicle is developed. The main focus of the contribution lies on the mathematical modeling of the self-supplied variable displacement axial piston units of the hydraulic system since they basically determine the performance of the overall torque control. Starting from a complex high-order dynamic model, a systematic order reduction of the nonlinear model is accomplished by means of singular perturbation theory. The accuracy of the derived models is evaluated by measurement results on an industrial test bench.